2016
DOI: 10.1002/cpp.1971
|View full text |Cite
|
Sign up to set email alerts
|

Different Perspectives of Clinicians and Patients with Severe Mental Illness on Motivation for Treatment

Abstract: Clinicians show poor to moderate capability in estimating how patients perceive their motivation for engaging in treatment, especially so when the patient's motives revolve around feelings of shame and guilt. Clinicians generally give higher motivation ratings for patients where they experience a higher quality therapeutic relationships with, whereas-depending on the scale that is used to measure motivation-they give lower ratings to patients who respond in socially desirable ways and to ethnic minority patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…This suggests that clinicians noticed a reduction in relatively external motivation for engaging in treatment in their patients in response to MF, signifying that their perception of the patient’s motivation has changed in response to the intervention. We have previously found that introjected motivation for treatment was especially difficult for clinicians to estimate in the current patient sample, 40 and it is therefore reasonable to assume that the repeated conversations with patients regarding their motives has led to a change in the clinician’s perception of the motivation such that it became more closely aligned with the patient’s perspective. As such, the intervention may have enhanced the clinician’s ability to estimate the patient’s perspective on motivation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This suggests that clinicians noticed a reduction in relatively external motivation for engaging in treatment in their patients in response to MF, signifying that their perception of the patient’s motivation has changed in response to the intervention. We have previously found that introjected motivation for treatment was especially difficult for clinicians to estimate in the current patient sample, 40 and it is therefore reasonable to assume that the repeated conversations with patients regarding their motives has led to a change in the clinician’s perception of the motivation such that it became more closely aligned with the patient’s perspective. As such, the intervention may have enhanced the clinician’s ability to estimate the patient’s perspective on motivation.…”
Section: Discussionmentioning
confidence: 90%
“…Numerous studies suggest that evaluation of the patient’s motivation may help understand how a patient may best be engaged in treatment, 1 5 while other studies have found that clinicians have difficulties in estimating their patient’s motivation for treatment, 40 suggesting that the plausibility of the rationale for the current study was high. However, it should be noted that in the Netherlands, the accessibility and quality of mental health care for patients with SMI are currently at a relatively high level.…”
Section: Discussionmentioning
confidence: 92%
“…None of the members of the sample were lost during the treatment and follow-up phases of the research, setting this study apart from others in which the sample attrition rate at five years exceeded 60% (Turkington et al, 2008).Refusal to participate in studies and abandonment during the course of a study are very common phenomena among the population examined here (Villeneuvea, Potvinc, Lesageb, & Nicolec, 2010), as patients often display a lack of motivation to undertake treatment (Jochems et al, 2015)and experience great difficulties in sustaining it.…”
Section: Discussionmentioning
confidence: 97%
“…For example, some researchers have looked at combining CBT with compassionate mind training therapy (CMT) (Beaumont, Galpin, & Jenkins, 2012), while others have examined the use of motivational interventions in cognitive therapy programs to treat psychosis Wai, Mui, Cheung, & Gray, 2015). In fact, patents' degree of motivation to start and maintain the therapy process has been found to play a critical role in determining the prognosis of a disorder (Jochems, van Dam, Duivenvoorden, Scheffer, van der Feltz-Cornelis & Niels, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into counselor‐client agreement have been conducted in the context of diverse relationships that counselors have with their clients with serious mental illnesses, such as treatment, counseling, vocational rehabilitation, and supportive services. Counselor‐client agreement has been investigated in the areas of (a) perceived needs for treatment (Lasalvia et al, 2000; Miyamoto et al, 2015), (b) vocational goals (Knaeps et al, 2015), (c) quality of life (Crocker et al, 2015), and (d) motivation for mental health treatment (Jochems et al, 2016). The cumulative results of these studies have suggested that counselors often report differing levels of functioning and needs than do their clients (Fitzpatrick et al, 2005; Holmqvist et al, 2016; Marfeo, Ni, Haley, Bogusz, et al, 2013; Tryon et al, 2007).…”
mentioning
confidence: 99%